The Iran-United States Tribunal’s Approach to Interpreting Paragraph 9 of the Algerian General Declaration: Lessons for the Future - Khalil Rouzegari Aghbolagh; Abdollah Abedini; Mojtaba Asgharian (پژوهش های حقوق تطبیقی)
Under Paragraph 9 of the “Declaration of the Government of the Democratic and Popular Republic of Algeria” (or the General Declaration) the US undertook to transfer Iranian properties to Iran. The Iran-United States Tribunal interpreted this paragraph of the Declaration in Partial verdicts Nos. 529, 601, 604, and 382. Generally speaking, the Tribunal interpreted the term “Iranian property” in Partial verdicts Nos. 529, 601, and 604 as tangible properties solely owned by Iran. To determine the ownership criterion, the Court considered the United States Uniform Commercial Code as the standard of practice, according to which the transfer of ownership as a general rule is subject to the delivery of the subject matter of the transaction to the buyer or customer. With this interpretation, the Court stated in Partial verdict No. 604 in many cases that due to the failure to transfer ownership of the disputed properties to Iran, the United States' obligation to transfer them to Iran was not enforceable. Given the thematic similarity of Case B-61 with Case A-15 (Two: A), the second stage of which requires the issuance of an verdict, assuming the applicability of the findings of partial verdict No. 604 in making a decision in Case B-61, the answer to this question becomes important: what arrangement can be considered to prevent this?